Near-infrared spectroscopy: more accurate than heart rate for monitoring intensity in running in hilly terrain - Born, D.-P.; Stöggl, T.; Swarén, M.; Björklund, G. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the cardiorespiratory and metabolic response of trail running and evaluate whether heart rate (HR) adequately reflects the exercise intensity or if the tissue-saturation index (TSI) could provide a more accurate measure during running in hilly terrain.